Off-design performance control and simulation for gas turbine engines with sequential combustors - Li, Yiguang; Liu, Yang (Sage, 2025)
A gas turbine engine with a sequential combustion system has the potential to offer high cycle efficiency at moderate turbine entry temperatures. Consequently, it has one more degree of power setting control, which offers more flexible but also more complex control of engine off-design operations. In this paper, a novel simulation method for off-design thermodynamic performance of sequential combustion gas turbines has been introduced and a novel performance control schedule for part-load operations at various ambient conditions have been proposed aiming to keep the relative workloads between the two turbine sections constant. The proposed control schedule is simple and can be adapted easily. By applying the off-design performance control schedule to a model industrial gas turbine engine with two sequential combustors, the performance of the model engine is simulated at different part-load and at different ambient conditions. The results show that by applying the proposed off-design performance control schedule, the model sequential combustion gas turbine engine could operate effectively at different part-load operating conditions and at different ambient conditions with both turbine sections keeping nearly constant workload distributions.
Keywords: Gas turbine; engine; reheat; sequential combustion; performance; simulation; control; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4010 Engineering Practice and Education; 4017 Mechanical engineering